$A$-cluster points via ideals - Gurdal, M.; Savaş, E. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Following the line of the recent work by Sava¸s et al., we apply the notion of ideals to $A$-statistical cluster points. We getnecessary conditions for the two matrices to be equivalent in a sense of $A^I$ -statistical convergence. In addition, we useKolk’s idea to define and study $B^I$ -statistical convergence.